2010
DOI: 10.3892/or_00000728
|View full text |Cite
|
Sign up to set email alerts
|

Radiosensitivity profiles from a panel of ovarian cancer cell lines exhibiting genetic alterations in p53 and disparate DNA-dependent protein kinase activities

Abstract: Abstract.The variability of radiation responses in ovarian tumors and tumor-derived cell lines is poorly understood. Since both DNA repair capacity and p53 status can significantly alter radiation sensitivity, we evaluated these factors along with radiation sensitivity in a panel of sporadic human ovarian carcinoma cell lines. We observed a gradation of radiation sensitivity among these sixteen lines, with a five-fold difference in the LD 50 between the most radiosensitive and the most radioresistant cells. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…Indeed, there is research reporting that decrease of single DNA-PKcs activity was not a major factor for damage sensitivity. 23, 24 Another interpretation is that DNA-PKcs-mediated phosphorylation of p53, a substrate of DNA-PKcs, 21, 25, 26, 27, 28 was decreased by Snail1 overexpression. Therefore, decreased p53 function by Snail1 may be also involved in the damage resistance, 29, 30 which resulted in damage survival and genomic instability.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is research reporting that decrease of single DNA-PKcs activity was not a major factor for damage sensitivity. 23, 24 Another interpretation is that DNA-PKcs-mediated phosphorylation of p53, a substrate of DNA-PKcs, 21, 25, 26, 27, 28 was decreased by Snail1 overexpression. Therefore, decreased p53 function by Snail1 may be also involved in the damage resistance, 29, 30 which resulted in damage survival and genomic instability.…”
Section: Discussionmentioning
confidence: 99%
“…No strong correlation between radiosensitivity and DNA-PKcs was found in a study of sporadic human ovarian cancer cell lines. The data suggested that DNA-PKcs copy number, expression level, or kinase activities are not reliable predictors of radiosensitivity in ovarian cancer ( 60 ). However, inhibition of DNA-PKcs has been shown by us to reverse cisplatin resistance in a panel of ovarian cancer cell lines ( 37 ).…”
Section: Dna-pkcs As a Therapeutic Target For Ovarian Cancermentioning
confidence: 99%
“…Variations in DSB repair and differences in DNA-PKcs levels have been reported earlier in a radiosensitization study of ovarian cancer cell lines. (Langland et al, 2010). The cell line dependent variations in various enzyme expression levels could be a factor in the differences in the degree of DSB repair inhibition seen in this study.…”
Section: Discussionmentioning
confidence: 73%